PENEGAKAN HUKUM TERHADAP ANAK DALAM PELANGGARAN LALU LINTAS YANG MENYEBABKAN HILANGNYA NYAWA ORANG LAIN DI KOTA SINGARAJA - Ida Ayu Putu Monika Dewi; Ni Putu Rai Yuliartini; Dewa Gede Sudika Mangku (Program Studi Ilmu Hukum, Jurusan Hukum dan Kewarganegaraan, Fakultas Hukum dan Ilmu Sosial, Universitas Pendidikan Ganesha, 2020)
An accident is an omission and negligence is a crime that is no criminal accountability, as set out in Article 310 of Law Number 22 Year 2009 regarding Traffic and Road Transportation. The issue when the accident committed by a child causing others died, how law enforcement against minors in the case accident resulting in loss of lives of others in the city of Singaraja. This study uses empirical legal research. Empirical legal research is a field research by relying on facts. Data were collected by interviews and by means of a literature study, methods of analysis with qualitative way to describe and interpret data based on the doctrine and legal norms relating to the subject of the obtain problem then arranged for the clarity of the issues discussed. Based on the research that writers get in law enforcement against children, generally from the data in the can since 2017 till 2019 there are 25 cases entered in the Police Buleleng, the solution is only at the stage of diversion in the police, because the child was 15 years old and is suspect as well as the penalties are less than 7 (seven) years, where the child has violated Article 310 paragraph (4) of Law Number 22 year 2009 regarding Traffic and Road Transportation.